1995
DOI: 10.1007/bf00173709
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of cells containing factor XIII subunit a around the foci of intense fibrosis in human epulides

Abstract: On the basis of clinical and biochemical findings, Factor XIII subunit a (FXIII A) has been conjectured to play an important role in fibrotic processes. Epulis samples at different stages of fibrotic tissue formation were used as a model system for studying the localization and tissue distribution of FXIII A during the course of connective tissue generation. Marker characteristics of cells containing FXIII A (FXIII A+ cells) were determined as well. In double immunofluorescent labelling systems, FXIII A was lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

1995
1995
2011
2011

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 35 publications
1
5
0
Order By: Relevance
“…A similar increase in the number of FXIII A + cells has been observed in our recent studies, in which a huge number of FXIII A--cells could be detected in several kinds of human fibrosing lesions (Toida et al, 1990b(Toida et al, , 1991(Toida et al, , 1995. The present findings suggest that FXIII A § cells, which can release FXIII A into the extracellular matrix, may play an important role in the processes of stromal desmoplasia and/or matrix reorganization in buccal squamous-cell carcinoma.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…A similar increase in the number of FXIII A + cells has been observed in our recent studies, in which a huge number of FXIII A--cells could be detected in several kinds of human fibrosing lesions (Toida et al, 1990b(Toida et al, , 1991(Toida et al, , 1995. The present findings suggest that FXIII A § cells, which can release FXIII A into the extracellular matrix, may play an important role in the processes of stromal desmoplasia and/or matrix reorganization in buccal squamous-cell carcinoma.…”
Section: Discussionsupporting
confidence: 66%
“…All of these monoclonal antibodies were raised in mice against human antigens. The characteristics of these antibodies are summarized elsewhere (Toida et al, 1995).…”
Section: Double Immunofluorescence Reactionsmentioning
confidence: 99%
“…The a-subunit of FXIIIa belongs to a family consisting of several genes that encode for enzymes with a common active-site structure, well conserved among species (17). Accumulating evidence points to an additional role for FXIIIa in prolifera-tion of connective tissues via its expression by invading macrophages (18,19). In this study, we discovered some characteristics of the a-subunit of FXIIIa in fish plasma that are distinct from those of its mammalian counterpart.…”
mentioning
confidence: 76%
“…In addition to its participation in blood coagulation, FXIIIa appears to be the extracellular TGase involved in wound healing (16,19,20). The mammalian PNS tissue, according to the present study, seems to respond very efficiently to injury, as shown for example by the fact that FXIIIa becomes fully active (i.e., could not be further activated by the addition of thrombin) as a result of sciatic nerve excision.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study we have shown that TGF-β co-localizes with the blood coagulation and wound healing protein XIII α in fibrotic lesions of carcinoid heart disease. Although the main function of XIII α is the cross-linking of fibrin molecules, it also takes part in wound healing and, as previous research indicated, in fibrotic processes [20, 21]. In this context it is noteworthy that fibrinogen and fibrin have been previously identified in carcinoid plaques [22].…”
Section: Discussionmentioning
confidence: 99%